2015
DOI: 10.1007/s11010-015-2450-y
|View full text |Cite
|
Sign up to set email alerts
|

Functions of miR-1 and miR-133a during the postnatal development of masseter and gastrocnemius muscles

Abstract: The present study investigated the function of miR-1 and miR-133a during the postnatal development of mouse skeletal muscles. The amounts of miR-1 and miR-133a were measured in mouse masseter and gastrocnemius muscles between 1 and 12 weeks after birth with real-time polymerase chain reaction and those of HDACs, MEF2, MyoD family, MCK, SRF, and Cyclin D1 were measured at 2 and 12 weeks with Western blotting. In both the masseter and gastrocnemius muscles, the amount of miR-1 increased between 1 and 12 weeks, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
(75 reference statements)
0
9
0
Order By: Relevance
“…Increased levels of microRNA‐1 can be also involved in postnatal myoblast differentiation by suppressing HDAC4, a predicted target gene of this myomiR . HDACs are well known for regulating muscle proliferation, differentiation, and growth through the regulation of histone acetylation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased levels of microRNA‐1 can be also involved in postnatal myoblast differentiation by suppressing HDAC4, a predicted target gene of this myomiR . HDACs are well known for regulating muscle proliferation, differentiation, and growth through the regulation of histone acetylation.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, class IIa HDACs (HDACs 4, 5, 7, and 9) plays an important role in the maintenance of muscle mass and protein degradation during muscle wasting . The reduced levels of HDAC4 promote myoblast differentiation, while increased levels of HDAC4 enhances skeletal muscle atrophy . Chen et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, many miRNAs have been shown to regulate the proliferation and differentiation of myoblasts during muscle myogenesis. Previous studies have reported that several miRNAs, including miR-1 13 , 14 , miR-133 15 , 16 and miR-206 17 , 18 , are muscle-specific miRNAs because their key regulators are involved in muscle myogenesis in humans, mice and cows. Some non-specific miRNAs in muscle, such as miR-24 19 , miR-26a 20 , miR-29 21 , miR-125b 22 , miR-181 23 , miR-214 24 and miR-491 25 , are also essential for the regulation of muscle myogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…These miRNAs also play roles in muscle development in mammals. Previous studies reported that several miRNAs, such as miR-1, 47 miR-133, 31,45,49 and miR-206, 3,19,42 are musclespecific miRNAs because they are key regulators in muscle development in human, pigs, and rats. Others miRNAs may also contribute to muscle development.…”
Section: Introductionmentioning
confidence: 99%